Frederic William Wile scrapbooks - Wile, Frederic William, 1873-1941.
Scrapbooks (circa 5,000 items) chiefly containing clippings of news stories, dispatches, and columns written during Wile's career in journalism. Subjects include his service as an intelligence specialist on German affairs with the American Expeditionary Forces during World War I, the London Naval Conference (1930), and the Conference for the Reduction and Limitation of Armaments, Geneva, Switzerland (1932-1934). Includes a telegram (1909) from Frederick Albert Cook regarding his alleged discovery of the North Pole.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Journalist, foreign correspondent, and radio commentator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Scrapbooks discarded after microfilming except for selected items placed in MMC-3564 (circa 100 items : 1 container : 0.2 linear feet).
Keywords: Cook, Frederick Albert, -- 1865-1940.; United States. -- Army. -- American Expeditionary Forces; Disarmament; World War, 1914-1918 -- Military intelligence; World War, 1914-1918 -- Germany; North Pole -- Discovery and exploration; Arctic regions -- Discovery and exploration; Foreign correspondents; Journalists; Radio journalists